Fall risk among urban community older persons - Mary J. T. Valera (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
The elderly should be screened in the community for risk for falls. It impacts significantly on their ability to still be active and productive even during aging. This study determined the risk for falls among Philippine urban community-dwellers 65 years old and above. Participants were ambulatory elderly peopleregistered in a government centre in one city. Data collection was done by interviewing elders and assessing fall risk factors. Data analyses were done using descriptive statistics and SPSS version 16 was used to correlate variables. Fall risk predictive factor is age. 63.3% of the participants are categorized as young-old to middle old. Protective factor fall risk is being married and/or living with family, which is 65.3% of this group. Confidence level in performance and completion of tasks were measured by Activity-Based Confidence (ABC), which showed 71.5% has moderate level of confidence. However, confidence level isinsufficiently-proven by literature to predict falls. Depression is statistically significant related factor for falls and was measured by Geriatric Depression Scale (GDS). Results showed that 87.7% has mild depression. Functional mobility capacity of the participants, namely balance and gait, and flexibility were measured by Tinetti Balance and Gait Scores (TBGS) and Chair Sit-and-Reach Test (CSRT), respectively. TBGS yielded 46.9%, and CSRT yielded 67.3%, which is low risk for falls. Correlation between TBGS and GDS, and TBGS and ABC were arrived at by using Spearman Rho. It yielded a significant relationship (r = 0.358, p = 0.012) between balance and gait with a depressive state, and no significant relationship (r = -0.136, p = 0.352) between balance and gait with confidence level, respectively